Smallholder farmers’ perceptions and strategies for adaptation to climate change in Brong Ahafo and Upper West Regions of Ghana - Abdoulaye, Tahirou; Bamire, Simeon Adebayo; Akinola, Adebayo A.; Etwire, Prince M. (2017)
With data collected from 750 farming households using survey questionnaire and 25 Focus Group Discussions (FGD), this report documents farmers’ perception of climate change and adaptation strategies in the Brong Ahafo and Upper West regions of Ghana. Results showed that DTM varieties are a viable strategy for adaptation to climate change. The use of drought tolerant or early maturing varieties ranked among the top three adaptation strategies used by farmers to combat risks from climate change in their production activities. Other strategies include growing different crops or engaging in mixed cropping and changing planting dates. The key determinant of DTM adoption in Brong Ahafo is occurrence of drought shock. In Upper West, farmers’ age, awareness about climate change, distance from input markets, access to credit, and training on DT varieties affect the probability of adoption of DTM. Widespread adoption of DTM has the potential of minimising farm-level impacts of climate change in Ghana.